Modified Lignin–PVOH and Epoxy Adhesives for Engineered Wood - Yanran Sun; Xueping Qiu; Xingxian Lan (BioResources, 2025)
Lignin-based adhesives are promising eco-friendly alternatives to petroleum-derived resins, but they face challenges in bonding strength and water resistance. This study presents a dual chemical modification strategy—phenolation and hydroxymethylation—to enhance the reactivity and polarity of industrial lignin. The modified lignin was blended with polyvinyl alcohol (PVOH) and epoxy resin to formulate adhesives suitable for engineered wood applications. Among the tested formulations, the PVOH-lignin adhesive reached a tensile shear strength of 7.8 MPa with 85% strength retention after water immersion, while the epoxy-lignin adhesive achieved 9.5 MPa with enhanced thermal resistance. Structural characterization using FTIR and 1H-NMR confirmed the successful introduction of functional groups. To reduce energy consumption, a low-temperature and low-pressure curing process based on microwave-assisted heating and mechanical stirring was implemented, reducing energy use by 40% compared to conventional heating methods. Life cycle assessment (LCA) results indicated a 40% lower carbon footprint and 50% reduction in volatile organic compound (VOC) emissions relative to petroleum-based adhesives. These results demonstrate the feasibility of using chemically modified lignin in high-performance adhesive systems for engineered wood while improving environmental sustainability.